Surface modulation and back reflection from foil targets irradiated by a Petawatt femtosecond laser pulse at oblique incidence - Ter-Avetisyan Sargis; Andreev Alexander; Platonov K.; Sung J. H.; Lee S. K.; Lee H. W.; Yoo J. Y.; Singh P. K.; Ahmed H.; Scullion C.; Kakolee K. F.; Jeong T. W.; et al. (2016)
A significant level of back reflected laser energy was measured during the interaction of ultra-short, high contrast PW laser pulses with solid targets at 30 degrees incidence. 2D PIC simulations carried out for the experimental conditions show that at the laser-target interface a dynamic regular structure is generated during the interaction, which acts as a grating (quasi-grating) and reflects back a significant amount of incident laser energy. With increasing laser intensity above 1018 W/cm(2) the back reflected fraction increases due to the growth of the surface modulation to larger amplitudes. Above 1020 W/cm(2) this increase results in the partial destruction of the quasi-grating structure and, hence, in the saturation of the back reflection efficiency. The PIC simulation results are in good agreement with the experimental findings, and, additionally, demonstrate that in presence of a small amount of pre-plasma this regular structure will be smeared out and the back reflection reduced. (C) 2016 Optical Society of America
Keywords: Fizikai tudományok